An introduction to finance - Thornham, Roger (London : Financial i Production, 1992)
This video consists of three videos. The videos discussed on the need for financial markets, market structure, secondary markets, risk & return, equity, bonds, money markets, foreign exchange and risk management products
Three videos in one container + one book of trainer's guide
Copy available in DVD format
Executive producer, Colin G. Sullivan ; writer, Warren F. Smith
Keywords: Finance; Money market; Foreign exchange